Frequency response of a beam-like structure to moving harmonic forces - Khiem, Nguyen Tien; Hang, Phi Thi (Vietnam Journal of Mechanics, 2016)
The spectral approach is employed for spectral analysis of a beam subjected to an arbitrary force traveling along the beam with constant speed. First, an expression for exact frequency response of a beam subjected to moving arbitrary force and general boundary conditions has been constructed. The obtained frequency domain response allows straightforwardly exhibiting response vibration components governed by different frequencies such as the natural, loading and driving ones and their interaction. This provides also alternative insight to the cancellation of response at natural frequency. The theoretical development is illustrated and validated by numerical examination on a simply supported beam under moving harmonic forces.